COMPARISON OF KELAKAI AND KATUK EXTRACT COMBINATION TO 0.2% CHLORHEXIDINE GLUCONATE AGAINST Porphyromonas gingivalis - Erisa Lidiya; I Wayan Arya Krishnawan Firdaus; Fransiska Uli Arta Panjaitan (Dentin, 2023)
Background: Periodontal disease is the second most frequent oral disease in Indonesia, which includes periodontitis. Porphyromonas gingivalis is the predominant bacteria in chronic periodontitis. This disease is usually treated with 0.2% chlorhexidine gluconate mouthwash. However, 0.2% chlorhexidine gluconate has several adverse effects, such as tooth discoloration, irritation of the oral mucosa, and changes in taste sensation. Therefore, an herbal-based mouthwash is needed. A combination of kelakai leaf and katuk leaf extract contains antibacterial substances such as flavonoid, tannin, steroid, alkaloid, and saponin, which can be used as an alternative therapy for chronic periodontitis. Purpose: To compare the inhibitory zone of kelakai and katuk extract combination with 0.2 Chlorhexidine gluconate against Porphyromonas gingivalis. Method: True experimental design with 13 treatment groups and 3 repetitions for each group. The treatment groups include combinations of kelakai leaf extract with 25%, 50%, 75%, 100% concentrations and katuk leaf extract with 20%, 40%, 80% concentrations and 0.2% chlorhexidine gluconate, which were tested on Porphyromonas gingivalis with a total of 39 samples. The inhibitory zone is measured with caliper after incubated for 48 hours.  Results: One-Way ANOVA revealed significant differences between all treatment groups and 0.2% chlorhexidine gluconate. Consequently, the Bonferroni post-hoc test was performed, which showed that the antibacterial activity of 75% kelakai leaf and 80% katuk leaf extract did not differ significantly from the activity of 0.2% chlorhexidine gluconate. Conclusion: The combination of 75% kelakai leaf and 80% katuk leaf extract has an equal antibacterial activity to 0.2% chlorhexidine gluconate against Porphyromonas gingivalis statistically. Keywords : 0.2 % Chlorhexidine gluconate, chronic periodontitis, combination of kelakai and katuk leaf extract, inhibitory activity, Porphyromonas gingivalis